2022
DOI: 10.1200/go.22.00030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Molecular Tumor Board on the Clinical Management of Patients With Cancer

Abstract: PURPOSE Multidisciplinary molecular tumor boards (MTBs) help in interpreting complex genomic data generated by molecular tumor profiling and improve patients' access to targeted therapies. The purpose of this study was to assess the impact of our institution's MTB on the clinical management of patients with cancer. METHODS This study was conducted at a tertiary cancer center in India. Cases to be discussed in the MTB were identified by molecular pathologists, scientists, or oncologists. On the basis of the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…A retrospective study showed that for a substantial proportion of patients there were no decided treatment plans before a thoracic MDTB and in close to 50% of those who had a previous plan of management, a change in plan resulted from the MDTB discussion [ 11 ]. Another recent assessment of the benefits of molecular MDTB showed similar advantages in terms of changes in management plans or a need for a new test [ 12 ]. The above two studies justify continuing with the MDTBs in helping make decisions for cancer patients.…”
Section: Reviewmentioning
confidence: 99%
“…A retrospective study showed that for a substantial proportion of patients there were no decided treatment plans before a thoracic MDTB and in close to 50% of those who had a previous plan of management, a change in plan resulted from the MDTB discussion [ 11 ]. Another recent assessment of the benefits of molecular MDTB showed similar advantages in terms of changes in management plans or a need for a new test [ 12 ]. The above two studies justify continuing with the MDTBs in helping make decisions for cancer patients.…”
Section: Reviewmentioning
confidence: 99%
“…A recent study reported that doctors complied with MTB recommendations to make changes in treatment plan for 58% of the patients studied (N = 138). 9 To our knowledge, our study is the first from a non–high-income country to investigate the discordance between NGS treatment recommendations and MTB recommendations. We found the discordance to be 49% with low level of evidence listed as the most common discordance rationale (75%) in our study.…”
Section: Discussionmentioning
confidence: 93%
“…To the best of our knowledge, this is the first multicenter, nationwide precision medicine study that utilizes cMTB for all participants. While discussions on MTBs may positively affect treatment decisions [ 22 ], increase the likelihood of enrollment in clinical trials, and potentially improve clinical outcomes [ 23 ], the associated turnaround time and cost might prevent the adoption of MTB in clinical practice [ 24 ]. Additionally, MTBs have not been actively employed in many Korean institutions because of disparities in human resources, infrastructure for NGS interpretation, and clinical trial access [ 9 ].…”
Section: Discussionmentioning
confidence: 99%